LEGIC RATIO OF MEDICINE LIABILITY IN RESOLVING CRIME TO LIFE PERSPECTIVE OF FORENSIC MEDICINE - Jadmiko, Widhi; Yahya, Koko Roby (UNES Law Review, 2023)
Crime as an act that has been determined by the State as a crime in its criminal law and is threatened with a sanction. By studying and researching acts that are declared by law as criminal acts. Crime as a legal delict is in the form of actions which, although not specified in law as a criminal event, are perceived as acts that are contrary to the legal system. It is very possible for a crime against life to occur for anyone who becomes a victim of a crime committed by the perpetrator. Crimes that kill a person can be intentional or negligent on the part of the perpetrator against the victim. The intention to kill almost all of a person's life because of an intention or plan to kill the victim by the perpetrator because there is a clear intention and the goal is that even life is negligent, for example, it is not an intention to kill so that as a result of the perpetrator's actions a person may lose his life. Surgical obligations in resolving crimes against lives has an important role because it is very possible for everyone to become a victim of a crime by the perpetrator. Crimes that kill a person can be intentional or negligent on the part of the perpetrator against the victim. So that there are cases of murder that require evidence of post-mortem examination. It is very interesting indeed when a case where the murder victim is not known with certainty the cause of someone's death requires the discipline of forensic medicine.